Synthesis and characterization of acrylated epoxidized soybean oil for UV cured coatings - Habib, Firdous; Bajpai, Madhu (Publishing House of Lviv Polytechnic National University, 2011)
This paper investigates the curing of biodegradable polymer films which were synthesized from soybean oil through the ultraviolet radiation and their stability against thermal degradation. In this study the epoxidation of soybean oil has been carried out via peracetic method. Further, an epoxy acrylate resin was synthesized from the epoxidized soybean oil (ESO) by using acrylic acid monomer. Triethylamine (TEA) and hydroquinone were used as a catalyst and inhibitor respectively. The acrylation of epoxidized soybean oil (AESO) is done by introducing acrylic acid, which is an unsaturated monomer into oxirane groups of the epoxidized oil (ESO). This reaction was confirmed by analytical data in terms of oxirane oxygen content, acid value, viscosity and spectral analysis. Different UV curable formulations have been investigated using synthesized acrylated resin and trifunctional acrylate monomer used as crosslinkable active diluents with photoinitiator. Monomer used was trimethylolpropane trimethacrylate (TMPTMA) while photoinitiator used was benzophenone along with an activator dimethyl ethanol amine (DEA). The mixtures were cured to make thin polymeric films under UV radiation with optimum irradiation dosing time of 20 min to produce the excellent cured coating which exhibits good thermal stability of about 473 K. В роботі досліджено затвердіння біодеградабельних полімерних плівок, синтезованих з соєвої олії за допомогою ультрафіолетового випромінювання, і їх стійкість до термічного розкладання. Епоксидування соєвої олії проводилось за допомогою надоцтового методу. Синтезовано епоксидну акрилатну смолу з епоксидованої соєвої олії з використанням акрилових мономерів кислоти. Як каталізатор та інгібітор відповідно використано триетиламін і гідрохінон. Акрилування епоксидованої соєвої олії проводилось внаслідок введення акрилової кислоти, яка є ненасиченим мономером, в оксиранові групи олії. Перебіг реакції підтверджено аналітичними даними стосовно вмісту оксиранового кисню, кислотним числом, в'язкістю і спектральними методами аналізу. Досліджено різні УФ-затверджені композиції, використовуючи синтезовані акрилатні смоли і трифункціональні акрилатні мономери як активні активні розчинники, зшиті з фотоініціатором. Як мономер використовували триметилолпропан триметилакрилату, а як фотоініціатор - бензофенон. Активатором слугував диметилетаноламін. Суміші були затверджені під ультрафіолетовим випромінюванням з оптимальним дозуванням опромінення 20 хв. для одержання тонких полімерних плівок, які можуть бути викорситані для виробництва термостійких (вище 473 К) покриттів.
Cинтез та характеристика акрилованої епоксидованої соєвої олії для УФ-затвердженого покриття
Keywords: epoxidation; acrylation; UV curing; coating; епоксидування; акрилування; УФ-затвердіння; покриття